Stabilization of the 53,000-dalton nonviral tumor antigen is not required for transformation by simian virus 40. - Sompayrac, L M (1983)
We have isolated a simian virus 40 deletion mutant, F8dl, that lacks the sequences from 0.168 to 0.424 map units. The deleted sequences represent about one-half of the coding region for large T antigen. We present evidence here that F8dl is able to transform mouse cells in a focus assay and that cell lines derived from these foci exhibit fully transformed phenotypes, have integrated mutant genomes, and express mutant-encoded proteins. This result implies that the region of the simian virus 40 genome between 0.168 and 0.424 map units is not essential for the maintenance of transformation. In addition, we have found that cells fully transformed by F8dl produce a 53,000-dalton nonviral tumor antigen (p53) that is as unstable as the p53 of untransformed cells. From this result we infer that transformation by simian virus 40 does not require the stabilization of p53.